Creative Economic Development Strategy in Malang City - Sopanah, A; Bahri, S; Ghozali, M (KnE Social Sciences, 2018)
Creative economy is a growing concept based on creative assets that potentially generate economic growth and progress. It contributes significantly to the economic growth of Malang City. The main purpose of this research was to develop the strategy of creative economy development in Malang City. The other purpose also updated the sub-sector creative economic data, identifying the challenging problems in development of creative economy. This research method used descriptive qualitative approach with SWOT analysis. The populations of this research were MSMEs (UMKM) that was engaged in creative economy. The results represented that from 1100 MSMEs in Malang City, 620 were engaged in the creative economy. Other research results indicated that the challenging problems in development of creative economy between sub-sectors somewhat varied. In general, among others, business model of creative industry has not yet been optimal, lack of appreciation to local creativity, limited marketing distribution, the susceptible creative industry institutions, and limited capital development. Given these shortcomings, this research has succeeded in formulating general development and each sector strategies. Keywords: creative economy, creative industry, UMKM, SWOT analysis, Malang City